2017
DOI: 10.14453/aabfj.v11i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Ethical Decision Making: Linking Moral Intensity, Self-Consciousness and Neutralization Techniques

Abstract: The purpose of the study is to examine the effect of moral intensity on self-conscious emotions and neutralization techniques in the context of ethical decision making among consumers. A sample of 388 shopping mall retail consumers was recruited through self-administered survey technique. Descriptive statistics, exploratory factor analysis, correlation was carried out in SPSS whereas the measurement model and structural relationships were estimated using AMOS.Results indicate that moral intensity positively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(114 reference statements)
0
3
0
2
Order By: Relevance
“…The results obtained indicate that self-consciousness affects consumer adoption of online shopping. According to Shah and Amjad [28], private self-consciousness obtained the highest scores, closely followed by public self-consciousness and, at a greater distance, by social anxiety. Our results indicate a stronger relationship between public self-consciousness and self-insecurity than in the Gould and Barak [14] study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained indicate that self-consciousness affects consumer adoption of online shopping. According to Shah and Amjad [28], private self-consciousness obtained the highest scores, closely followed by public self-consciousness and, at a greater distance, by social anxiety. Our results indicate a stronger relationship between public self-consciousness and self-insecurity than in the Gould and Barak [14] study.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a consumer who is high in private self-consciousness but low or neutral in public self-consciousness and social anxiety is the consumer profile that best explains the adoption of the electronic ticket. Shah and Amjad [28] analyzed self-consciousness with its three dimensions and found that self-consciousness moderates the relationship between moral intensity and neutralization techniques in the context of ethical consumer decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Persepsi yang timbul seperti ini disebut sebagai fenomena social anxiety. Individu yang merasakan fenomena tersebut memiliki ketidaknyamanan tersendiri yang diakibatkan karena merasa kurangnya kecakapan dalam menggunakan teknologi sehingga timbul perasaan takut apabila ketidakcakapannya dilihat dan dinilai tidak baik oleh orang lain (López-Bonilla, Sanz-Altamira, & López-Bonilla, 2021; Shah & Amjad, 2017). Jika dilihat pada konteks penggunaan ticket-vending machine di stasiun kereta yang tergolong ramai, tentunya persepsi seperti ini menurunkan motivasi para individu untuk menggunakan self-service technologies yang telah disediakan penyedia layanan kereta api secara masif.…”
Section: Pendahuluanunclassified
“…Ketidaknyamanan umumnya terjadi atas ketakutan seorang individu atas penilaian orang lain yang dirasa memperhatikan atau mengawasi tindakan yang sedang dilakukan, terutama di situasi keramaian. Hal ini menyebabkan timbulnya rasa malu sehingga berusaha menghindari diri dari melakukan suatu hal tertentu sebelum orang lain menciptakan persepsi yang tidak diinginkannya (Shah & Amjad, 2017).…”
Section: Pengembangan Hipotesisunclassified
“…The moral strength dimensions are found to be an important determinant of moral judgment. Individuals with a higher sense of responsibility are likely to evoke a higher level of self-consciousness when confronted with an ethical situation (Kong, et al, 2022;Shah & Amjad, 2017).…”
Section: Moral Intensitymentioning
confidence: 99%